Blind spot in lung cancer lymph node metastasis: Cross‐lobe peripheral lymph node metastasis in early stage patients. Issue 4 (8th March 2018) - Li, Ning; Tan, Fengwei; Li, Jiagen; Shao, Kang; Zhao, Jun; Mu, Juwei; Gao, Shugeng; He, Jie
Abstract : Background: At present, it has not yet been determined whether metastasis can be transferred cross‐lobe to peripheral lymph nodes (LNs) from other lobes in early stages of lung cancer, especially without any direct involvement to the pleura and parenchyma of the lobe. This study was conducted to investigate this issue. Methods: A retrospective analysis was conducted at the Chinese Academy of Medical Sciences. Patients undergoing right middle and lower lobectomy with lymphadenectomy for preoperative clinical stage Ia–IIIa from 2014 to 2015 were identified. To avoid interference, cases were limited to tumors within the primary lobe. When a tumor is completely located in the lower lobe, no direct invasion occurs into the visceral pleura/bronchus/parenchyma of the middle lobe and tumor cell metastasis into the peripheral LNs (stations 12–14) in the middle lobe is defined as cross‐lobe lymph node metastasis (CLM). Results: A total of 68 patients were identified, of which nine (13.2%) had CLM. Seven had squamous cell carcinoma, one adenocarcinoma, and one small cell carcinoma. Seven cases (77.8%) had intermediate bronchus invasion, and seven cases (77.8%) intermediate bronchus adjacent lymph node involvement (station 11). Compared to non‐CLM patients, tumor diameter (5.2 vs. 3.2; P = 0.28), N2 lymph node metastasis rate (66.7% vs. 28.8%; P = 0.03), late stage (IIIa 77.8% vs. 35.6%; P = 0.04), and invasion of intermediate bronchus (77.8% vs. 45.8%; P = 0.07) relatively increased. Conclusion: Non‐primary lobe peripheral LN metastasis exists in lung cancer and requires greater attention and further study.